Characterization of Antennal Sensilla and Immunolocalization of Odorant-Binding Proteins on Spotted Alfalfa Aphid, Therioaphis trifolii (Monell) - Song, Limei; Wang, Xuemin; Liu, Yanqi; Sun, Yinpeng; Ban, Liping (Frontiers in Physiology, 2020)
Abstract The spotted alfalfa aphid (Therioaphis trifolii (Monell), Homoptera, Drepanosiphidae) is a well-known destructive pest that can significantly reduce alfalfa yields. Herein, the morphology of antennal sensilla of T. trifolii have been examined by using scanning electron microscopy and the ultrastructure of sensilla stellate and placoidea were described by transmission electron microscopy. Stellate sensilla, placoid sensilla, and coeloconic sensilla were found on the 6th segment, and a single sensillum placoidea was located on the 5th segment. Placoid sensilla were also present on the 3rd antennal segment of alate and apterous aphids, and the number was similar between two morphs. Two types of trichoid sensilla and coeloconic sensilla were found on the antennae, respectively. The results of ultrastructure showed stellate sensilla are innervated by 3 neurons, while placoid sensilla present three groups of neurons, equipped with 2-3 dendrites in each neuron group. Immunocytochemical localization of odorant-binding proteins (OBPs) was performed on ultrathin sections of sensilla stellate and placoidea, and we observed that the antiserum against OBP6 intensively labeled all placoid sensilla from both primary and secondary rhinaria. OBP7 and OBP8 could also be detected in placoid sensilla, but less strongly than OBP6. In addition, OBP6, OBP7, and OBP8 were densely labelled in stellate sensilla, suggesting OBP6, OBP7 and OBP8 may sense alarm pheromone-germacrene A in T. trifolii.